1999
DOI: 10.1021/ma981791g
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonates from Sugars:  Ring-Opening Polymerization of 1,2-O-Isopropylidene-d-Xylofuranose-3,5- Cyclic Carbonate (IPXTC)

Abstract: A number of applications in biomedical materials will greatly benefit by further research in bioresorbable polymers that have various side group attributes. By careful design, these functional groups can be used to regulate hydrophilicity/hydrophobicity, permeability, bioresorption and mechanical properties. 1-3 The pendant functional groups provide active sites for crosslinking and grafting as well as the opportunity to attach bioactive substances to modulate cellular responses for tissue engineering applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 29 publications
(69 reference statements)
1
68
2
Order By: Relevance
“…10,[26][27][28][29] Pendant hydroxyl groups have been introduced to improve the hydrophilicity and hence the degradability. 30 Since end groups have special effect on degradation rate, end-group functionalized polycarbonates will have different degradation rate. Because the polymers of multiarm architecture have a higher end-group concentration than linear polymers of the same molecular weights, the multiarm structure can strengthen the end group effect.…”
Section: Introductionmentioning
confidence: 99%
“…10,[26][27][28][29] Pendant hydroxyl groups have been introduced to improve the hydrophilicity and hence the degradability. 30 Since end groups have special effect on degradation rate, end-group functionalized polycarbonates will have different degradation rate. Because the polymers of multiarm architecture have a higher end-group concentration than linear polymers of the same molecular weights, the multiarm structure can strengthen the end group effect.…”
Section: Introductionmentioning
confidence: 99%
“…[2] It is well known that copolymerization is an effective way of providing materials with different properties. The properties of PTMC also can be tailored by copolymerization of trimethylene carbonate (TMC) with other cyclic monomers, such as glycolide, [3] lactide, [4] e-caprolactone, [5] 1,4-dioxan-2-one, [6] cyclic phosphates, [7] as well as other cyclic carbonates, [8] in order to meet different needs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For their synthesis, various procedures have been used, that is, (i) the polycondensation between the carbonate derivatives and diols, 4 (ii) the ring-opening polymerization of cyclic carbonates, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and (iii) the alternating polymerization of epoxides with carbon dioxide. Among these procedures, the ring-opening polymerizations of cyclic carbonates have the potential to control the molecular weight and to induce copolymerization with other cyclic monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Six-membered cycles (or larger) using anionic initiators tend to polymerize smoothly, yielding the corresponding polycarbonate at a lower temperature (o100 1C). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In contrast, the anionic ring-opening polymerization of the fivemembered ring is thermodynamically unfavorable and proceeds at a higher temperature (4150 1C), causing the elimination of carbon dioxide to produce a copolymer that consists of both carbonate and ether linkages. [20][21][22][23][24][25] However, we reported that the anionic ringopening polymerization of a five-membered cyclic carbonate (MBCG) (Figure 1) possessing the a,D-glucopyranoside structure proceeded even at 0 1C to produce an aliphatic polycarbonate without the elimination of carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%